Analyzing the short term and long-term complication of hysterectomy: a prospective study - N. R., Sindhu; Rao, Bharathi Divakar; Zubair, Sabah Mohd. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Hysterectomy is the most common surgical procedure done worldwide in women. Although many studies were done regarding short term complications, long term complications are not very well followed up. The objective of the study is to analyze short term and also long-term complications for the different mode of hysterectomy. Methods: It was a time-bound hospital-based prospective study which includes all the women who underwent hysterectomy for benign conditions in the hospital except women with prior psychiatric, bowel, bladder and sexual dysfunctions. All the patients were followed up for one year using a set of questionnaires to study short term and long-term complications. Results: No significant difference in short term post-operative complications concerning the mode of hysterectomy except for UTI was more common in vaginal hysterectomy group and haemorrhage in TAH route. Sexual dysfunction was noted even after 1 year of surgery in all modes of hysterectomy. Mild urinary dysfunction found statistically significant even at 1 year follow up in vaginal hysterectomy mode however there was no bothersome urinary dysfunction persistent after one year. Conclusions: Sexual dysfunction is the most common persistent long-term morbidity following hysterectomy found in the present study.